A history of forensic anthropology. Issue 4 (25th March 2018) - Ubelaker, Douglas H.
Abstract: Forensic anthropology represents a dynamic and rapidly evolving complex discipline within anthropology and forensic science. Academic roots extend back to early European anatomists but development coalesced in the Americas through high‐profile court testimony, assemblage of documented collections and focused research. Formation of the anthropology section of the American Academy of Forensic Sciences in 1972, the American Board of Forensic Anthropology in 1977/1978 and other organizational advances provided important stimuli for progress. While early pioneers concentrated on analysis of skeletonized human remains, applications today have expanded to include complex methods of search and recovery, the biomechanics of trauma interpretation, isotopic analysis related to diet and region of origin, age estimation of the living and issues related to humanitarian and human rights investigations.